The potential anticoagulant property of Caulerpa lentillifera crude extract - Arenajo, Althea R.; Ybanez, Adrian P.; Ababan, Maria Maichol P.; Villajuan, Charlotte E.; Lasam, May Rose M.; Young, Chiqui P.; Reyes, Julie Lynn A. (International Journal of Health Sciences, 2017)
Background: Anticoagulants have been used in the treatment of several circulatory diseases and thrombotic disorders, and in the blood sampling for hematologic analysis. Sulfated polysaccharides (SP), which have anticoagulant properties, are found in most seaweeds, including Caulerpa spp. Objective: The study generally aimed to evaluate the potential anticoagulant property of Caulerpa lentillifera. Methodology: The whole plant of fresh C. lentillifera was washed thoroughly with distilled water and manually expressed to obtain the extract. C. lentillifera extract was tested in two phases. Phase one utilized nine male albino rabbits, which were randomly and equally allocated into three groups: (1) negative control (oral distilled water and subsequent in vitro mixing of extracted blood with normal saline solution), (2) positive control (oral aspirin and subsequent in vitro mixing of extracted blood with normal saline solution), and (3) experimental group (oral distilled water and in vitro mixing of extracted blood with C. lentillifera extract). Blood coagulation was evaluated by measuring the clotting time using the slide and tube methods. In phase two, peripheral blood from three apparently healthy adult dogs were used. Blood collection was performed thrice. In each collection, the sample was divided into five aliquots: (1) negative control (normal saline solution), (2) positive control (ethylenediaminetetraacetic acid [EDTA]), and (3-5) experimental treatments at 0.1, 0.15, and 0.2 ml of C. lentillifera extract. Coagulation was evaluated by measuring the clotting time using the tube method. Results: Phase one results revealed significant differences on the clotting time between the negative and the positive and experimental groups (P < 0.05), and no significant differences on the clotting time between the positive and the experimental groups (P > 0.05). In phase two, all blood samples mixed with EDTA did not clot, while the negative control had an average clotting time of 2.01 min. Blood mixed with 0.2 ml of C. lentillifera extract had the longest coagulation time (15.49 min). Simple linear regression revealed a positive significant correlation (multiple R = 0.9450, R2 = 0.8931, P = 0.02) implying dose-dependent anticoagulant potential. The study showed that C. lentillifera extract may have a potential anticoagulant property due to its component SP.